PATH50 Novelty-seeking and risk-taking behaviour in subtypes of Parkinson's disease. Issue 11 (22nd October 2010) - Singh-Curry, V; Bunzeck, N; O'Sullivan, S; Molloy, M; Perry, R; Bain, P; Lees, A; Duzel, E; Husain, M
Abstract : Why do some patients with Parkinson's disease develop risk-taking behaviour? We assessed responses to novelty and willingness to take risks in 29 patients with idiopathic Parkinson's disease (PD), compared to elderly controls and 14 PD patients with impulse control disorders (ICD). Participants were assessed on tasks designed to probe novelty processing and risk-taking behaviour. Akinetic-rigid PD patients, as well as those with ICD, were significantly quicker to respond to novel compared to nonnovel perceptually salient stimuli. By contrast tremor dominant PD patients and controls responded equally quickly to both types of stimuli. Faster reaction times to novel stimuli correlated with greater risk-taking on the Iowa Gambling Task for akinetic–rigid PD patients only. Importantly, there was no association between these measures and l -dopa equivalent dose. Instead, preserved structural integrity of mesolimbic regions (assessed with magnetisation transfer imaging) correlated with novelty-seeking in PD patients without ICD and increased risk-taking in the ICD patients. Akinetic-rigid patients tended to have higher levels of structural integrity here than tremor dominant patients. These results suggest that preservation of the mesolimbic dopaminergic system may play an important role in the development of ICD. Furthermore, our findings suggest akinetic–rigid patients may be more susceptible to developing these problems.